The arbuscular mycorrhizal fungus Rhizophagus irregularis uses a reductive iron assimilation pathway for high‐affinity iron uptake. (23rd April 2018) - Tamayo, Elisabeth; Knight, Simon A. B.; Valderas, Ascensión; Dancis, Andrew; Ferrol, Nuria
Summary: Arbuscular mycorrhizal (AM) fungi can improve iron (Fe) acquisition of their host plants. Here, we report a characterization of two components of the high‐affinity reductive Fe uptake system of Rhizophagus irregularis, the ferric reductase ( RiFRE1 ) and the high affinity Fe permeases ( RiFTR1‐2 ). In the extraradical mycelia (ERM), Fe deficiency induced activation of a plasma membrane‐localized ferric reductase, an enzyme that reduces Fe(III) sources to the more soluble Fe(II). Yeast mutant complementation assays showed that RiFRE1 encodes a functional ferric reductase and RiFTR1 an iron permease. In the heterologous system, RiFTR1 was expressed in the plasma membrane while RiFTR2 was expressed in the endomembranes. In the ERM, the highest expression levels of RiFTR1 were found in mycelia grown in media with 0.045 mM Fe, while RiFTR2 was upregulated under Fe‐deficient conditions. RiFTR2 expression also increased in the intraradical mycelia (IRM) of maize plants grown without Fe. These data indicate that the Fe permease RiFTR1 plays a key role in Fe acquisition and that RiFTR2 is involved in Fe homeostasis under Fe‐limiting conditions. RiFTR1 was highly expressed in the (IRM), which suggests that the maintenance of Fe homeostasis in the IRM might be essential for a successful symbiosis.